ASPEK HISTORIS INDUSTRI OLAHRAGA - Syallomita Pompayo (STIKES Columbia Asia Medan, 2024)
The sports industry has undergone significant transformations since the 19th century. Since the emergence of modern organized sports in the era of the industrial revolution, sports have become more than just physical activities, but a means of expressing national identity and a political tool. The main findings show that industrialization created the conditions for the development of professional sports, while the post-war era was marked by the globalization of sports and the emergence of the mass media as a significant actor in the commercialization of sports. By understanding the historical aspects of the sports industry, this research contributes to a deeper understanding of how sport developed into a global phenomenon involving various economic, political, and cultural sectors.